Successful Innovative Minimal Invasive Splenectomy in a Child with Combined Congenital Immunodeficiency and Acquired Pancytopenia Secondary to Hypersplenism - Anthony, Favour Mfonobong; Govani, Dhaval; Patel, Rasila; Patel, Ramnik (Journal of Hematology Research, 2021)
Congenital combined immunodeficiency in association of acquired hypersplenism are uncommon lesions in pediatric patients and certainly poses several diagnostic and therapeutic challenges for successful and safe outcome of ideal treatment which has consequences of life long precautions. Herein, we report a case of combined immunodeficiency complicated by hypersplenism and pancytopenia in a 4-year-old female toddler who presented with hypogammaglobulinemia, low circulating B cells, and T cell lymphopenia, anemia and thrombocytopenia. The results of hematological investigations revealed pancytopenia with ongoing persistent anemia, thrombocytopenia and leukopenia. and bone marrow examination revealed adequate cellularity with normally functioning bone marrow and no circulating auto antibodies. A splenectomy using an innovative minimal invasive technique was performed for curative purposes. Any evidence of the recurrence of hypersplenism was not noted 30 months after the operation. Surgery is the most frequently performed treatment for hypersplenism with pancytopenia and normal bone marrow and no circulating antibodies. Pre-operative and post splenectomy vaccination record and post splenectomy status cards provide additional precautions for rare but life-threatening post splenectomy complications.